Enhancing Military Communication Skills through Needs-Based EMP: A Current and Target Situation Analysis - Martha Patricia Purba; Selviana Napitupulu (Yayasan Bayt Shufiya Nusantara, 2026)
English has become an essential communication tool in modern military contexts, particularly in multinational operations and international cooperation. However, many military personnel still experience difficulties in using English effectively for professional communication. This study aims to examine the role of English for Military Purposes (EMP) in enhancing military personnel’s communication skills. The research employed a descriptive qualitative design using a library research method and needs analysis guided by ESP theory. The findings reveal that while reading skills are dominant for interpreting technical manuals, there is a significant gap in speaking and listening proficiency required for operational tasks. The study concludes that a needs-based and task-oriented EMP program, incorporating authentic materials and simulations, can significantly improve communication effectiveness and confidence in military professional settings.